Intertextuality In Online News Coverage Of The 2011 Jasmine Revolution: A Comparison Between Aljazeera And Bbc Arabic - Muhammad Marwan Ismail; Farah Nadia Harun (Sciendo, 2024)
Baltic Journal of Law and Politics Volume 15 No.1 Page (1066-1081)